DEVELOPING A RESILIENT SURVIVAL MODEL FOR MALAYSIAN SMEs: A CONCEPTUAL PAPER - Sharifah Syakila Syed Shaharuddin; Nurul Amira Azmi; Mohamad Hanif Abu Hassan; Wahidah Shari; Muhammad Zarunnaim Haji Wahab (International Journal of Accounting, Finance and Business, 2023)
The study endeavours to devise a sturdy survival plan for small and medium-sized enterprises (SMEs) in Malaysia, ensuring their continued existence during crisis situations, such as the COVID-19 pandemic. Using both quantitative and qualitative methods like questionnaire distribution and focus group discussions with an expert moderator, the research will deliberate on theories of contingency and reinforcement. Additionally, it will review earlier literature to formulate a conceptual framework concentrating on areas like leadership qualities, operational techniques, dynamic capabilities, and IT support that might assist these SMEs endure such emergency circumstances. This newly proposed model may aid policymakers or managers in coordinating initiatives towards SME stability after crises by suggesting resilience strategies that increase competitiveness. As this investigation identifies measures necessary for SME survival following prolonged upheavals specifically in developing regions; it complements existing management literature. Furthermore, since the research aligns with Malaysia's National Entrepreneurship Policy 2030 mission to transform into an entrepreneurial country - makes its findings significant.